The Influence of Media Leaflet on Increasing Knowledge of Reproductive Health of Brides-to-Be in Padang City - Iffah, Uliy; Safaringga, Miranie; Ridwan, Laila Hijradesy; Maharani, Putri (CV. Green Publisher Indonesia, 2024)
According to WHO (2019), the Maternal Mortality Rate is the number of maternal deaths resulting from pregnancy, childbirth, and postpartum processes, which are used as indicators of women's health status. Maternal Mortality Rate (MMR) is one of the global targets of the Sustainable Development Goals (SDGs) to reduce maternal mortality (MMR) to 70 per 100,000 live births by 2030. Several efforts to reduce MMR have been carried out by the Padang City government, including implementing the Childbirth Planning and Prevention of Complications (P4K) Program, using MCH books, implementing classes for pregnant women, and health counseling activities. This quantitative research uses a pocketbook of the bride and groom using leaflet media. This is a guide for brides-to-be as part of marriage advice and guidance for those who have registered their marriage at the Regional Office of Religious Affairs (KUA). The subject of this study was a bride-to-be in Padang City. Providing reproductive health counseling on women's knowledge in premarital preparation in the working area of KUA Koto Tangah District has an influence.